Silence of the Administration in the Current Macedonian Administrative Dispute Legislation and the Necessity of Amendments - Bitrakov, Konstantin (Iustinianus Primus Faculty of Law, 2021)
The Assembly of the Republic of North Macedonia (hereinafter: Macedonia or North Macedonia) adopted a new Law on Administrative Disputes in May 2019, thus commencing the third phase of the administrative dispute development in the country. The respective Law on Administrative Disputes came into force one year later, precisely on the 25th of May 2020. Generally speaking, multiple novelties in the administrative dispute regime were introduced with the adoption of the referenced law: (*) the scope of the administrative dispute was broadened; (*) new principles on which the administrative dispute is based upon were introduced; (*) the administrative judiciary was bound to pay attention to the consistency of adjudications (which, one might argue, is a step closer to developing a case-law system); (*) the administrative judiciary can now fine the public authorities which do not cooperate; (*) the new institutes of model-procedure and model-decision were introduced, etc. In that context, the Law of Administrative Disputes from 2019 may serve as a point of reference when speaking of positive reforms in terms of judicial oversight over the public authorities. However, the Law on Administrative Disputes also changed the rules for filing a lawsuit in the cases of “silence of the administration”, that is situations when the administration does not adopt the decision (individual administrative act) within the statutory deadlines. The objective of this article is to explain the new rules for filing a lawsuit due to silence of the administration are less favourable for the citizens. The relevant provisions of the Law on Administrative Disputes from 2019 should be restructured so that they fit the old regime for silence of the administration. While it is certain that the topic at hand is indeed narrow, it is of utmost importance that the relevant provisions of the Law on Administrative Disputes are amended as soon as possible since they would harm citizens interests in a scale rather difficult to foresee.
Keywords: silence of the administration, administrative dispute, Law on Administrative disputes, lawsuit